2020
DOI: 10.3390/cancers12103028
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin Interacting Protein (TXNIP) Is Differentially Expressed in Human Tumor Samples but Is Absent in Human Tumor Cell Line Xenografts: Implications for Its Use as an Immunosurveillance Marker

Abstract: Thioredoxin interacting protein (TXNIP) is a metabolic protein critically involved in redox homeostasis and has been proposed as a tumor suppressor gene in a variety of malignancies. Accordingly, TXNIP is downregulated in breast, bladder, and gastric cancer and in tumor transplant models TXNIP overexpression inhibits growth and metastasis. As TXNIP protein expression has only been investigated in few malignancies, we employed immunohistochemical detection in a large multi-tumor tissue microarray consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Studies by Jing Zhao et al (2019) have shown that GBP1 can promote survival or carcinogenesis in prostate cancer. TXNIP is the only known α-arrestin protein family that binds to Trx (Schröder et al, 2020). The expression of TXNIP in tumors is very low, and it may play an inhibitory role in many kinds of cancers such as liver cancer, breast cancer and lung cancer (Chen et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Jing Zhao et al (2019) have shown that GBP1 can promote survival or carcinogenesis in prostate cancer. TXNIP is the only known α-arrestin protein family that binds to Trx (Schröder et al, 2020). The expression of TXNIP in tumors is very low, and it may play an inhibitory role in many kinds of cancers such as liver cancer, breast cancer and lung cancer (Chen et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…The study further revealed that TXNIP , CAV1 , GABARAPL1 , and TSC22D3 may play key roles in the regulation of ferroptosis in GC. TXNIP , a metabolic protein, has been considered to be a tumor suppressor gene in various malignant tumors, and its overexpression can suppress the growth and metastasis of cancer cells in tumor transplant models 32 . TXNIP is downregulated in GC than in normal tissues and has been shown to be a key marker for the prognosis of patients with gastric cancer 33 .…”
Section: Discussionmentioning
confidence: 99%
“…IKBIP, a gene not commonly reported in cancer data, was recently shown to be highly involved in EMT and was associated with more aggressive phenotypes in gliomas [107]. Finally, down-regulation of TXNIP, demonstrated in breast, bladder, and gastric cancer was recently shown to be a common feature in human tumor xenograft models in which intra-tumoral leukocytes are responsible for the decreased expression of TXNIP, suggesting that TXNIP expression levels can be used to monitor the functional state of tumor-infiltrating leukocytes [108]. Finally, it needs to be emphasized that several of our identified biomarkers in this study are overlapped with previously identified DEGs/DEPs in several endothelial cell lines with disruption of the CSC [109, 110], confirming the importance of the CmP network in the tumorigenesis of CAW-TNBCs.…”
Section: Discussionmentioning
confidence: 99%